2008
DOI: 10.1111/j.1365-2923.2001.00837.x
|View full text |Cite
|
Sign up to set email alerts
|

Career obstacles for women in medicine: an overview

Abstract: Purpose This article describes the current position of women in the ®eld of medicine.Procedures Material was gathered using a MEDLINE search for recent articles on women's career progress in medicine and data from the Association of American Medical Colleges.Main ®ndings Although women now make up a large proportion of the medical student body in industrialized nations, they are still under-represented in a number of disciplines and in the higher echelons of medicine. A number of possible obstacles to career g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 63 publications
1
18
0
1
Order By: Relevance
“…To date, however, no study has examined this topic adequately in medicine, and the few studies that touch on this topic are conflicting (19,23,46). Because academic medicine has been reluctant to adjust its traditional measures of success-such as publications and grants-to appropriately reward individuals who assume more of the teaching load, the promotion of women may be selectively slowed (71,79,85). Gender-based discrimination and harassment still occur in society.…”
Section: Academic Responsibilitiesmentioning
confidence: 99%
“…To date, however, no study has examined this topic adequately in medicine, and the few studies that touch on this topic are conflicting (19,23,46). Because academic medicine has been reluctant to adjust its traditional measures of success-such as publications and grants-to appropriately reward individuals who assume more of the teaching load, the promotion of women may be selectively slowed (71,79,85). Gender-based discrimination and harassment still occur in society.…”
Section: Academic Responsibilitiesmentioning
confidence: 99%
“…gender, family background, indebtedness and academic performance) affect medical students' choices of work location (urban or rural) [14,15], work status (full-time or parttime) [16], profession (surgeon, physician, general practitioner, etc.) [17], career success and drop-out rates [18].…”
Section: Introductionmentioning
confidence: 99%
“…Gender influences not only the specialty chosen, but also the reasons that contribute to making this choice. Valian (1999) suggested that men and women prefer specialties that are congruent to their gender schemas; females generally opt for pediatrics and gynecology-obstetrics (Jaafar & Ahmed, 1993;Kassebaum et al, 1996;AAMC, 1999;Reed & Fischer, 2001;Monleon-Moscardo et al, 2003) and men select surgical specialties (Monleon-Moscardo et al, 2003).…”
Section: Introductionmentioning
confidence: 99%